Engaging with the non-human turn: A response to Büscher. Issue 1 (March 2022) - Greco, Elisa
Büscher's recent article promoted a new language of 'more-than-human' and 'less-than-human' alongside the concept of surplus alienation from nature, observing that the non-human turn would benefit from an engagement with history. In commenting Büscher's intervention, I observe that the 'nonhuman turn' does not have much traction in the Global South, possibly because the alienation from nature is experienced through the violent realities of primitive accumulation. The non-human turn is hardly compatible with Marx's understanding of capital and nature–society relations as organised by the law of value. The new language of the non-human turn is founded on an idealistic conception of society and history, reproposing an analytically problematic 'we' that perpetuates class-blind analyses.